Clinical Characteristics of Coronavirus Disease 2019 - Rara Julia Timbara Harahap (Global Health Science Group, 2020)
The COVID-19 took the world by storm and has become a pandemic. It was first reported in Wuhan, Hubei province, China in December 2019. This virus is a new type of coronavirus. COVID-19 is caused by SAR-CoV2. The purpose of this study was to determine the clinical characteristics of COVID-19 including clinical symptoms and the tests used to confirm the disease. The research method used is literature review by collecting 25 journals from 2020, these journals were collected from various sources, namely Pubmed, Medscape, Google scholar and WHO, and only 22 articels were used in this study. The results obtained from this study are that it is known that the symptoms of COVID-19 are not specific and initially only mild symptoms such as fever, cough and fatigue and appear gradually. This disease can be confirmed using the rRT-PCR method, besides that a chest CT scan can also be done as a diagnostic test for COVID-19.